2022
DOI: 10.1057/s41292-022-00272-w
|View full text |Cite
|
Sign up to set email alerts
|

Making epistemic goods compatible: knowledge-making practices in a lifestyle intervention RCT on mindfulness and compassion meditation

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…As is well-known, the standard procedure used in clinical trials involves the comparison of a user group and a control group. This method was initially invented for the testing of drug treatments and continues to be used extensively for this purpose, even though it is not without problems (Lilienfeld 1982;Smolka 2022;Timmermans and Berg 2003). The dynamics of mindfulness therapy, as well as other behavioral therapy methods, however, differ significantly from drug treatments.…”
Section: Operationalizing Mindfulness: How To Observe a Solipsistic E...mentioning
confidence: 99%
See 2 more Smart Citations
“…As is well-known, the standard procedure used in clinical trials involves the comparison of a user group and a control group. This method was initially invented for the testing of drug treatments and continues to be used extensively for this purpose, even though it is not without problems (Lilienfeld 1982;Smolka 2022;Timmermans and Berg 2003). The dynamics of mindfulness therapy, as well as other behavioral therapy methods, however, differ significantly from drug treatments.…”
Section: Operationalizing Mindfulness: How To Observe a Solipsistic E...mentioning
confidence: 99%
“…But one obvious implication of this is that it becomes quite difficult to ascertain, for instance, whether two patients who report meditating 30 min per day are going through the same 'treatment'. In a recent pioneering study, Smolka (2022) has shown in detail the full scope of such complications, to which there is little to add. Here, however, I would like to focus on one fundamental problem that underlies most of the methodological challenges that mindfulness researchers face.…”
Section: Operationalizing Mindfulness: How To Observe a Solipsistic E...mentioning
confidence: 99%
See 1 more Smart Citation